BEBERAPA SYARAT CUKUP UNTUK BILANGAN KROMATIK LOKASI HINGGA PADA GRAF TAK TERHUBUNG - Des Welyyanti (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
The locating-chromatic number of a graph is introduced by Chartrand et al. in 2002. Firstly, Chatrand et al. determine the locating-chromatic number of path and double stars. The locating-chromatic number is an interesting concept ini graph theory. In this paper, we determine some condtions for disconnected graphs has a finite locating-chromatic number.